Penerapan Model Pembelajaran Kooperatif Tipe Rotation Trio Exchange Berbantuan Media Roda Putar Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas IV UPT SD Negeri 79 Ujung Tanah - Kadir, Abdul; Firdaus, Firdaus; Asrabiatul Wahdaniah (MACCA : Science-Edu Journal, 2025)
This research is a Classroom Action Research that aims to determine how the application of the Rotation Trio Exchange Cooperative Learning Model assisted by the Rotating Wheel media improves the Mathematics learning outcomes of fourth-grade students of UPT SD Negeri 79 Ujung Tanah. The subjects in this study were all 17 fourth-grade students and the fourth-grade homeroom teacher. Data collection techniques used observation and tests. Data analysis techniques include data reduction, data description, and drawing conclusions. The results showed that the percentage of teacher activity in cycle I meetings 1 and 2 each reached 67% (Enough). In cycle II, the percentage of teacher activity reached 67% (Enough) at meeting 1 and increased to 100% (Good) at meeting 2. The percentage of student activity in cycle I meetings 1 and 2 was also at 67% (Enough), but increased to 67% (Enough) at meeting 1 of cycle II and 100% (Good) at meeting 2 of cycle II. Student learning outcomes also increased significantly. In cycle I, the average score of students was 66 with a percentage of learning completion reaching 53% (Enough). In cycle II, the average score increased to 79 with a percentage of learning completion reaching 82% (Good). In conclusion, the RTE Type Cooperative learning model assisted by the Rotating Wheel media can improve the Mathematics learning outcomes of fourth grade students. This model is effectively applied as an innovative and interactive learning method.